Speech After Long Silence—An Appraisee-Based Comprehensive Analysis With Retrospective and Future Perspectives on Current ID Policy of Transpersons in China - Shi, Jian; Guo, Yadong; Cavagnaro, María José; Cai, Jifeng; Liu, Zhuoying (Frontiers in Public Health, 2021)
As the sexual minority in China, transpersons remain faced with various realistic challenges. In recent years, however, there has been a significant progress made in the protection given to the rights that transpersons deserve. Currently, the citizens who have changed their gender through sex reassignment surgery can make applications to the local police station for changing their gender registration and get issued a new ID card. This is regarded as a crucial milestone in reducing the bias against transpersons and protecting their legitimate rights in China. Highlighted by the case of an extraordinary appraisee who have received SRS to change from male to female and started a new life with a new ID, not only does this article construe the current ID policy and the detailed process of ID card change for transpersons in China, it also reveals the living and developmental conditions facing transpersons in China. Finally, the visibility of the community of transpersons is improved to eradicate the discrimination against transpersons.